Management control systems in Nepalese Commercial Banks / Jitendra Prasad Upadhyay - Upadhyay, Jitendra Prasad (Universiti Teknologi Mara Selangor, 2016)
Purpose – The purpose of this study is to examine whether the mechanisms of MCS have been adequately developed and applied in the Nepalese commercial banks or not. Methodology Used – Descriptive and analytical research designs have been used for the study. Primary data have been collected through the questionnaires using convenience and judgmental sampling from the Nepalese commercial banks. Questionnaires have been developed in five scales and mean, standard deviation, coefficient of variation, correlation and factor analysis have been used as tools. Cronbach’s alpha test has been done to test the reliability of the data. Findings – All the commercial banks have applied the mechanisms of MCS.